Development of a new ultrasound scoring system to evaluate glandular inflammation in Sjögren's syndrome: an OMERACT reliability exercise - İNANÇ, GÜZİDE NEVSUN (My University, 2022)
© The Author(s) 2021. Published by Oxford University Press on behalf of the British Society for Rheumatology. All rights reserved. For permissions, please email: journals.permissions@oup.com.OBJECTIVE: The aim of this exercise from the OMERACT Ultrasound subgroup on Sjögren\"s syndrome was to develop and assess the reliability of a consensus-based semiquantitative colour Doppler US scoring system for pathologic salivary gland vascularization in patients with primary Sjögren\"s syndrome (pSS). METHODS: Using the Delphi method, a colour Doppler semiquantitative scoring system for vascularization of bilateral parotid and submandibular glands was developed and tested in static images and on patients (9 pSS patients and 9 sonographers). Intra-reader and inter-reader reliability of grading the salivary glands were computed by weighted Cohen and Light\"s kappa analysis, respectively. RESULTS: The consensus-based semiquantitative score was: grade 0, no visible vascular signals; grade 1, focal, dispersed vascular signals; grade 2, diffuse vascular signals detected in 50% of the gland. In static images, the intra- and inter-reader reliability showed excellent kappa values (95% CI) of 0.90 (0.87, 0.93) and 0.80 (0.74, 0.84), respectively, for all four salivary glands together. In patients, the intra- and inter-reader reliability for all four salivary glands together was kappa = 0.84 (0.73, 0.92) and 0.70 (0.64, 0.76), respectively. CONCLUSION: The consensus-based colour Doppler US scoring for the evaluation of salivary gland vascularization in pSS showed a good inter-reader reliability and excellent intra-reader reliability in static images and in patients. The clinical application of the developed scoring system should be tested in clinical settings.
Keywords: Tıp; Temel Eczacılık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Farmakoloji ve Toksikoloji; ROMATOLOJİ; FARMAKOLOJİ VE ECZACILIK; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; PHARMACOLOGY & TOXICOLOGY; RHEUMATOLOGY; PHARMACOLOGY & PHARMACY; Romatoloji; Farmakoloji (tıbbi); Rheumatology; Pharmacology (medical); primary Sjogren's syndrome; salivary gland vascularization; colour Doppler ultrasound; scoring system; COLOR DOPPLER SONOGRAPHY; CLASSIFICATION CRITERIA; SALIVARY-GLANDS; CONSENSUS; primary Sjögren’s syndrome